2011
DOI: 10.1002/cncr.26038
|View full text |Cite
|
Sign up to set email alerts
|

Secondary malignancies among nonseminomatous germ cell tumor cancer survivors

Abstract: BACKGROUND: Men on active surveillance for clinical stage I nonseminomatous germ cell tumor (NSGCT) undergo frequent computed tomography imaging to avoid delayed detection of disease. Irradiation from frequent imaging and chemotherapy upon progression may place patients at increased risk of a second malignancy. In this study, the authors sought to identify such an increased risk among men who chose initial surveillance for NSGCT. METHODS: The authors utilized data from the Surveillance, Epidemiology and End Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…The use of RPLND to treat stage I NSGCT has been associated with a lower risk of secondary malignancy development. 32 The main long-term complications of RPLND are 30,[33][34][35] The risk of infertility increases with RPLND. 36 Compared with EBRT and CT, however, the fertility rates have been best in patients with testicular cancer who had undergone RPLND.…”
Section: Discussionmentioning
confidence: 99%
“…The use of RPLND to treat stage I NSGCT has been associated with a lower risk of secondary malignancy development. 32 The main long-term complications of RPLND are 30,[33][34][35] The risk of infertility increases with RPLND. 36 Compared with EBRT and CT, however, the fertility rates have been best in patients with testicular cancer who had undergone RPLND.…”
Section: Discussionmentioning
confidence: 99%
“…First, the main concern regarding observational studies is confounding by treatment selection bias (eg surgery is prescribed for younger patients and brachytherapy for patients at lower risk). Propensity score methods are being widely recommended in observational studies (41)(42)(43) to account for treatment selection bias and, thus, to identify the true treatment effects. It is worth pointing out that carrying out randomized clinical trials to compare different treatments presents considerable difficulties in these patients (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…compared to the normal population after BEP administration (26). Although Chamie et al (27) reported higher risk of secondary solid malignancy due to CT some studies report a 0.5-1% risk of hematological malignancy as a result of high-dose etoposide (28). The adverse effect of cisplatin-based CT on fertility and sexual function is not yet known (29).…”
Section: Discussionmentioning
confidence: 99%